Genomic variations and epigenomic landscape of the medaka inbred Kiyosu-Karlsruhe (MIKK) panel - Leger, Adrien; Brettell, Ian; Monahan, Jack; Barton, Carl; Wolf, Nadeshda; Kusminski, Natalja; Herder, Cathrin; Aadepu, Narendar; Becker, Clara; Gierten, Jakob; Hammouda, Omar T.; Hasel, Eva; et al. (Genome biology, 2022)
The teleost medaka (Oryzias latipes) is a well-established vertebrate model system, with a long history of genetic research, and multiple high-quality reference genomes available for several inbred strains. Medaka has a high tolerance to inbreeding from the wild, thus allowing one to establish inbred lines from wild founder individuals.